2011
DOI: 10.1186/1471-2105-12-s1-s9
|View full text |Cite
|
Sign up to set email alerts
|

UMARS: Un-MAppable Reads Solution

Abstract: BackgroundUn-MAppable Reads Solution (UMARS) is a user-friendly web service focusing on retrieving valuable information from sequence reads that cannot be mapped back to reference genomes. Recently, next-generation sequencing (NGS) technology has emerged as a powerful tool for generating high-throughput sequencing data and has been applied to many kinds of biological research. In a typical analysis, adaptor-trimmed NGS reads were first mapped back to reference sequences, including genomes or transcripts. Howev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 33 publications
1
14
0
Order By: Relevance
“…For example, the reads with "0,0" are exactly the same with the reference miRNAs. As reported previously [11,22,23], we also observed that the reference miRNAs from miRBase are not necessary the most abundant ones. The mapping results of all pre-miRNAs in 15 libraries are shown in Additional File 3 (the read counts are not normalized as TPM, transcript per million).…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…For example, the reads with "0,0" are exactly the same with the reference miRNAs. As reported previously [11,22,23], we also observed that the reference miRNAs from miRBase are not necessary the most abundant ones. The mapping results of all pre-miRNAs in 15 libraries are shown in Additional File 3 (the read counts are not normalized as TPM, transcript per million).…”
Section: Resultssupporting
confidence: 87%
“…As described in a previous study [22], the opposite-arm miRNAs are not necessarily kept at lower expression levels than the annotated ones. In this study, the opposite-arm miRNA of hsa-mir-1307 has a higher expression level than the annotated one in most libraries, except for SRX018968 and SRX018971.…”
Section: Resultsmentioning
confidence: 94%
“…So, the reads with presentation "0,0" are exactly the same with reference miRNAs. Examining the counts of all reads, it is not guaranteed that the reference miRNAs from miRBase are the most abundant ones, which was also observed by other studies [11,12,14]. The mapping result of all pre-miRNAs in G1245N and G1245T library can be accessed in Additional file 2 and 3.…”
Section: Resultsmentioning
confidence: 83%
“…After further investigation, more than 85% of the unknown category (data not shown) in the 2 libraries could not be mapped back to the human genome (hg19). Our previous study showed that such unmappable reads could be derived from the exon-exon junctions of novel alternative splicing transcripts or from the transcripts of infection viruses [44]. These unmappable reads warrant further investigation.…”
Section: Resultsmentioning
confidence: 99%